CONSERVATIVE THERAPY OF HYDATID DISEASE - Murtazayev Zafar Israfulovich; Baysariyev Shovkat Usmonovich; Shodiyarova Hilola Janonovna (Research Focus International Scientific Journal, 2023)
To improve the results of conservative therapy for hydatid disease. Materials and methods. In order to prevent and reduce relapses of the disease, 81 patients (26 with pulmonary echinococcosis, 45 with liver echinococcosis and 8 patients with combined pulmonary and liver echinococcosis received 3 courses of therapy) operated on for echinococcosis were given drug therapy with mebendazole. 197 patients (69 with pulmonary echinococcosis, 107 with liver echinococcosis and 21 patients with combined pulmonary and liver echinococcosis) were treated with albendazole at a dose of 12 mg/kg per day for 30 days (3 courses). Albendazole was used for therapeutic purposes in 38 patients. Results. Patients with hydatid disease received drug therapy in the postoperative period. 79 patients took mebendazole in an amount of 40 ml/kg body weight for 30–35 days. 197 patients took albendazole at a dose of 12 ml/kg body weight for 30 days. The anthelmintic effectiveness of the drugs mebendazole and albendazole was assessed on the basis of dynamic ultrasonography, MSCT and x-ray control. To assess the results of drug therapy, we used the parameters proposed by WHO experts (good and excellent results; satisfactory results; unsatisfactory results). The effectiveness of treatment of hydatid echinococcosis of the liver and lungs with albendazole ranged from 58.37% to 82.23%, relapses were noted on average in 17.77% of patients. Conclusions. With traditional and minimally invasive interventions for echinococcosis, subsequent preventive drug therapy with albendazole is urgently necessary.